O Supremo Tribunal Federal às voltas com a erosão democrática: tensão social, estresse institucional e federalismo na pandemia de Covid-19 - Samuel Pereira de Farias (2024)
This dissertation investigates the Federal Supreme Court (STF) during President Jair Bolsonaro's administration, especially the cycle that coincides with the health emergency resulting from the Covid 19 pandemic. This timeframe was chosen because it is und erstood that during these years the Court found itself more than a relevant actor on the political scene, as it has been for almost two decades under pressure from the Executive, with direct or indirect attacks over the last four years. This phase is c redited with accentuating what academic literature has called the process of erosion of constitutional democracies, including Brazil, through mechanisms typical of illiberal populism. The research hypothesis is that the Federal Supreme Court, despite immen se institutional stress, has managed to act as an agent of containment of illiberal populism and democratic erosion during the Covid 19 pandemic, especially in the affirmation of Brazilian federalism. The research objective is to understand how the Federal Supreme Court has acted in the recent conjuncture (2019 2023) and whether the court may have acted as an agent of resistance to illiberal populism, as the Bolsonaro government will be characterized, and come to contain the deepening of democratic erosion in Brazil focusing on the context of the health crisis. It begins with an overview of the state of the art literature on democratic erosion and illiberal populism. Next, a brief overview is given of Brazilian federalism and the Supreme Court's decision making tendency, which points to a greater prevalence of the Union's interests (centralism) to the detriment of the states and municipalities. Federalism was chosen as a marker for the analysis because it is believed that the federal conflict appeared during the health crisis as a point of tension between the Executive headed by President Jair Bolsonaro and the other political entities, and could be chosen as a reliable marker for analyzing the possible containment of Bolsonaro's illiberal populism. We then move on to study the units of analysis (the selected court cases), before justifying the choice of the qualitative sample. The following cases were analyzed in this study: ADI 6.341, ADI 6.343 and ADPF 672, in which the STF confronted the issue of the division of powers between federal entities in the face of populist actions by the Federal Executive Branch in dealing with the Covid 19 pandemic. The research is qualitative in nature, and the methodology employed will be the case study technique, through which the Supreme Court's involvement with politically sensitive issues involving aspects of Brazilian democratic erosion will be analyzed. The co nclusion is that the research hypothesis is partially confirmed, pointing to the Supreme Court's contribution to containing illiberal populism, without, however, it being possible to make a broader inference regarding the total containment of illiberal populism.